2013
DOI: 10.4306/pi.2013.10.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Development and Standardization of Extended ChaeLee Korean Facial Expressions of Emotions

Abstract: ObjectiveIn recent years there has been an enormous increase of neuroscience research using the facial expressions of emotion. This has led to a need for ethnically specific facial expressions data, due to differences of facial emotion processing among different ethnicities.MethodsFifty professional actors were asked to pose with each of the following facial expressions in turn: happiness, sadness, fear, anger, disgust, surprise, and neutral. A total of 283 facial pictures of 40 actors were selected to be incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…With regard to the low hit rates and overlap between some facial expression ratings observed in the current study, the low agreement rate for fearful and disgust faces is not uncommon in other sets of facial expressions (Gur et al, 2002; Goeleven et al, 2008; Lee et al, 2013), except for Langner et al (2010). In particular, Ekman and Friesen (1986) mentioned that disgust and anger are often confused with one another, and Yrizarry et al (1998) reported that Japanese and Caucasian raters perceive multiple emotions in each basic emotion.…”
Section: Discussionmentioning
confidence: 49%
“…With regard to the low hit rates and overlap between some facial expression ratings observed in the current study, the low agreement rate for fearful and disgust faces is not uncommon in other sets of facial expressions (Gur et al, 2002; Goeleven et al, 2008; Lee et al, 2013), except for Langner et al (2010). In particular, Ekman and Friesen (1986) mentioned that disgust and anger are often confused with one another, and Yrizarry et al (1998) reported that Japanese and Caucasian raters perceive multiple emotions in each basic emotion.…”
Section: Discussionmentioning
confidence: 49%
“…For the dot-probe task, we selected faces with angry (valence 1.82 ± 0.06; arousal 3.81 ± 0.12), happy (valence 4.14 ± 0.15; arousal 3.01 ± 0.07), and neutral (valence 2.74 ± 0.15; arousal 2.51 ± 0.10) expressions from a standardized database of face photographs (Lee et al, 2013). Valence and arousal ratings were based on a 5-point scale (1 = extremely unpleasant/not at all arousing, 5 = extremely pleasant/extremely arousing).…”
Section: Methodsmentioning
confidence: 99%
“…We used the Korea University Facial Expression Collection (KUFEC). 10 In comparison with other Korean facial stimuli sets (e.g., Korean Facial Expressions of Emotion and Extended ChaeLee Korean Facial Expressions of Emotions), 13 , 14 the KUFEC was selected because it offers a greater number of facial stimuli (KU-FEC=6126) and was reported ratings of valence and arousal levels for each stimulus, which allowed for the examination of multiple aspects of a stimulus. Developing an FER task for sc-hizophrenia research involved three steps.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, the Extended ChaeLee Korean Facial Expressions of Emotions, which consists of 259 facial expression stimuli created using 37 actors (16 male, 21 female, age range 26-60 years), was standardized. 14 These sets of Korean facial emotion stimuli have been extensively used in basic laboratory research in Korea over the past decade. 15 , 16 , 17 , 18 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%